DINAMIKA KELOMPOK PEMBUDIDAYA IKAN “MAWAR” DI KECAMATAN BERINGIN KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA - Kusai Kusai; Lamun Bathara; Johana Johana (Fakultas Perikanan dan Kelautan, Universitas Riau, 2013)
This research was conducted in Juli 2012 at Beringin subdistrict Deli Serdangdistrict of North Sumatera province. It was aimed to found determine whatcaused the goal has not been achieved and to found out the dinamycs level with toknow its group dynamic factors that influence the dynamics level of fish farmergroup MawarThe research was using case study methode, by collecting informationdirectly, interview by using questioner and observation. Determination of therespondents used the census where the number of respondents in research were allmambers of the group of Mawar that add up to 20 people. The results of researchgroups indicates purpose has not been achieved because the absence of a cleartask structure and the absence of norms/ sanctions within the groupMawar so thatthe members are still working on group activities with the will ordesire of eachmember. Level of dynamics group Mawar are in the category of dynamic 2681.While the factors that affect the level of dynamics group Mawar is factor taskfunction, factors group building and maintenance, factor group cohesiveness,factor group atmosphere, factor group pressure,factor group effectiveness, and thefactorhidden agenda group.Keywords : Dynamics, Fish Farmer Group, Factors